2007
DOI: 10.1002/cphc.200700127
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Geometry Change of the Phenol Dimer upon Electronic Excitation

Abstract: The change of the phenol dimer (PH2) structure upon electronic excitation is determined by a Franck-Condon analysis of the intensities in the fluorescence emission spectra obtained via excitation of seven different vibronic bands. A total of 547 emission band intensities are fitted, together with the changes of rotational constants upon electronic excitation of fi ve isotopomers. These rotational constants are taken from previously published [Schmitt et al. ChemPhysChem 2006, 7, 1241-1249] high-resolution LIF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 70 publications
7
13
0
Order By: Relevance
“…For the p CR dimer α changes from 54° to 32° while β changes from 17° to 53°. The same observations were made earlier for the PH dimer27, 33 as well as the hydroquinone dimer 34. In the aromatic dimers, the smaller value of α in the electronic ground state compared to that of the p CR⋅H 2 O and p ‐CR⋅MeOH complexes is because of the C 2D H 2D ⋅⋅⋅O A hydrogen bonding, which is absent in case of the H 2 O and MeOH complexes.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…For the p CR dimer α changes from 54° to 32° while β changes from 17° to 53°. The same observations were made earlier for the PH dimer27, 33 as well as the hydroquinone dimer 34. In the aromatic dimers, the smaller value of α in the electronic ground state compared to that of the p CR⋅H 2 O and p ‐CR⋅MeOH complexes is because of the C 2D H 2D ⋅⋅⋅O A hydrogen bonding, which is absent in case of the H 2 O and MeOH complexes.…”
Section: Discussionsupporting
confidence: 79%
“…The dispersion interaction plays a vital role in determining the structure and stabilization energy of the p CR dimer and the PH dimer, to which the π⋅⋅⋅π and CH⋅⋅⋅π interactions contribute significantly. Moreover recently has been demonstrated by Kleinermanns et al27 that the PH dimer structures obtained at these two levels of theory match well with the experimentally determined structure. In addition it was observed that the structural parameters of the complexes obtained using RICC2‐CP/TZVP level match well with the experimental values (vide infra).…”
Section: Results and Analysissupporting
confidence: 69%
See 2 more Smart Citations
“…In other cases, T, V and HB structures of (phenol) 2 35 and (p-cresol) 2 36 homodimers, and of 7-azaindole…fluoropyridines, 37 indole…pyridine, 38 indole…imidazole, 39 anisole…phenol, 40 and 7-azaindole…phenol 41 heterodimers have been experimentally observed. These structures are believed to be observed because of their remarkable stability in the ground state, as compared to other possible isomers.…”
Section: Introductionmentioning
confidence: 95%